Higher monomeric C-reactive protein levels are associated with premature coronary artery disease - Melnikov, Ivan; Kozlov, Sergey; Okhota, Sergey; Saburova, Olga; Avtaeva, Yuliya; Kuznetsova, Tatiana; Guria, Konstantin; Prokofieva, Lyudmila; Riazantseva, Tatiana; Ji, Shang-Rong; Wu, Yi; Gabbasov, Zufar (Frontiers in Immunology, 2025)
IntroductionChronic inflammation is a major risk factor for coronary artery disease (CAD). Currently, the inflammatory cardiovascular risk is assessed via C-reactive protein (CRP) levels measured using a high-sensitivity assay (hsCRP). Monomeric CRP (mCRP) is a locally produced form of CRP that has emerged as a potential biomarker of inflammation.AimThis study investigated whether mCRP levels are associated with premature CAD.Materials and methodsThis study comprised 103 participants of both sexes, including 50 patients 56 ± 7 years old with premature CAD and 53 patients 51 ± 10 years old without CAD. CAD was verified using coronary angiography, hsCRP levels were measured using a standard assay, and mCRP levels were measured using fluorescent cytometric beads conjugated with an anti-mCRP antibody.ResultsThe levels of hsCRP were 0.99 (0.59; 3.10) mg/L vs. 0.63 (0.35; 1.85) mg/L (p = 0.067), and mCRP 6.84 (4.20; 13.78) µg/L vs. 2.57 (0.32; 5.66) µg/L (p <0.001) in patients with CAD vs. patients without CAD, respectively. There was a weak positive correlation between the mCRP and hsCRP levels (ρ = 0.214; p = 0.030). hsCRP levels were below 2.0 mg/L (i.e., residual inflammatory cardiovascular risk should have been excluded) in 70% of patients with CAD and 79% of patients without CAD (p = 0.365). mCRP levels differed between the groups of patients with hsCRP levels below 2.0 mg/L: 5.14 (4.07; 10.68) µg/L vs. 2.77 (0.53; 5.00) µg/L in patients with or without CAD, respectively (p <0.001). Logistic regression analysis demonstrated that mCRP levels were independently associated with premature CAD. The adjusted odds ratio was 1.18 (95% CI 1.06-1.33, p = 0.004) per each µg/L increase in mCRP levels.ConclusionHigher mCRP levels were associated with premature CAD, independent of hsCRP levels and traditional risk factors.